The ARCCRABP1 neurons play a crucial role in the regulation of energy homeostasis - Lihong Yan; Xin Zhang; Liling Jin; Yin Li; Yang Chen; Jubiao Zhang; Zhenning Sun; Junxia Qi; Changqing Qu; Guanzhong Dong; Yongjie Zhang; Qin Jiang; et al. (Nature Communications)
Abstract Recent single-cell RNA sequencing study suggested that CRABP1 expressing neurons in the arcuate nucleus (ARCCRABP1 neurons) were a distinct group of neurons. However, the physiological role of ARCCRABP1 neurons remains unexplored. Here, we demonstrated that ARCCRABP1 neurons played a crucial role in regulation of energy homeostasis in male mice. Ablation of ARCCRABP1 neurons resulted in obesity and a diabetic phenotype in mice. By employing chemogenetic or optogenetic manipulation techniques, the inhibition and activation of ARCCRABP1 neurons resulted in an increase and decrease in food intake, respectively. The axon terminals from these ARCCRABP1 neurons project to several brain regions implicated in feeding regulation such as PVH, BNST, PBN, and NTS. Optogenetic manipulation of these axons within these brain regions resulted in significant alterations of food intake behavior in mice. Furthermore, the electrophysiological studies demonstrated that the activation of ARCCRABP1 neurons induces depolarization in POMC neurons in the hypothalamus. The hormone stimulation studies showed that most of the ARCCRABP1 neurons respond to insulin. Collectively, our findings demonstrate that ARCCRABP1 neurons represent a distinct neuronal subtype involved in energy homeostasis regulation.